STUDENT'S NUMERICAL ABILITY PROFILE REVIEWED BY GENDER - Salim Salim; La Masi; Wa Ode Fauziah (STAI Hubbulwathan Duri, 2020)
The purpose of this study is to describe the numerical abilities of male and female students in grade VIII of SMP Negeri 10 Kendari; and to analyze the differences in numerical abilities of male and female students in grade VIII of SMP Negeri 10 Kendari. This type of research is quantitative descriptive research with the population in this study is all grade VIII students of SMP Negeri 10 Kendari which number 157 students. Sampling using total sampling techniques selected a sample of 157 students as well. Data collection techniques use students' numerical ability tests. Based on the results of the data analysis and discussion obtained conclusions: (1) numerical ability reviewed gender for grade VIII students of State Junior High School 10 Kendari is in the low category of both male and female students; (2) no difference in the numerical ability of Grade VIII students of SMP Negeri 10 Kendari is reviewed by gender.